ANALISIS PENJADWALAN DENGAN PERCEPATAN PELAKSANAAN MENGGUNAKAN METODE PENAMBAHAN JUMLAH TENAGA KERJA DAN JAM KERJA - LALU WIRAHMAN WIRADARMA; ZAEDAR GAZALBA; TETI HANDAYANI (Universitas Mahasaraswati K. Mataram, 2023)
This study aims to analyze the factors that cause delays and analyze the time and cost of the acceleration method with the addition of the number of workers and the addition of working hours to obtain a more efficient comparison of the acceleration method for project completion. As for the steps in this study, namely the collection of data in the form of questionnaire results and existing project data, including the Budget Plan (RAB), Analysis of Work Unit Prices (AHSP) and Time Schedule. Factors causing project delays based on questionnaires were analyzed using interest index calculations with validity and reliability testing, in order to obtain the top ranking of factors causing delays with a value of ????ℎ = 0.502 < ???????? = 0.576 with